Discovery and Exclusion Prospects for Staus Produced by Heavy Higgs Boson Decays at the LHC - Arganda, Ernesto; Martín-Lozano, Victor; Medina, Anibal D.; Mileo, Nicolas I. (Advances in High Energy Physics, 2022)
In a previous work, we developed a search strategy for staus produced by the decay of the heavy CP-even Higgs boson H within the context of the large tanβ regime of the minimal supersymmetric standard model (MSSM) in a scenario of large stau mixing. Here, we study the performance of such search strategy by confronting it with the complementary mixing pattern in which decays of both the CP-even and CP-odd heavy Higgs bosons contribute to the production of τ~1τ~2∗+c.c pairs. Again, we focus on final states with two opposite-sign tau leptons and large missing transverse energy. We find that our proposed search strategy, although optimized for the large stau mixing scenario, is still quite sensitive to the complementary mixing pattern. We also extend the results reported in the preceding work for the large mixing scenario by including now the exclusion limits at the next run of the LHC and the prospects both for exclusion and discovery in a potential high-luminosity phase. Finally, we discuss the possibility to distinguish the two mixing scenarios when they share the same relevant mass spectrum and both reach the discovery level with our search strategy.